Характеристика великої рогатої худоби сірої української породи за еритроцитарними антигенами - Подоба, Б.Є.; Гузєв, І.В.; Сидоренко, О.В.; Гузєєв, Ю.В. (Фактори експериментальної еволюції організмів, 2013)
Aims. Establishment of features of evolution immunogenetic structures of Ukrainian Grey breed of cattle by erythrocytic antigenes. Methods. Livestock of pedigree plant «Polivanovka» analyzed on materials of testing during 1970–2005 by erythrocytic antigenes, which established in hemolytic tests by the standard technique, with use of monospecific wheys – reagents for definition of factors of groups of blood. Results. A significant variety erythrocytic antigenes and the increased antigenic saturation of the analysed population of native Ukrainian Grey cattle is established. At thoroughbred rearing the spectrum of antigenes inherent in breed and their increased total frequency is kept. Conclusions. The antigenic structure of breed is characterized by the increased frequencies of a significant amount of factors of groups of blood which are kept during the 30-years period.

Key words: biodiversity, genetic markers, erythrocytic antigenes, Ukrainian Grey breed.